Implementasi Aplikasi Peminjaman Ruang Rapat Berbasis Web Di Sekolah Vokasi Universitas Sebelas Maret - Andy Supriyadi (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2022)
A meeting room is a designated place where you and your team can participate, brainstorm, and have important conversations. It is an essential part of any office space and can help improve workflows. A meeting room is worth considering. An effective meeting room can include sharing ideas, working through feedback and obstacles, and more discussion related to improving the Tri-Dharma. Sebelas Maret University Vocational School has several meeting rooms in different denominations, but the reservation process was done manually using Microsoft Excel. There were some problems in the reservation process, one of the main problems is that a meeting room can be claimed to hold different meetings at the same time and at the same time. This research attempts to examine the implementation of a web-based reservation process. This application was built using open source based PHP and Mysql. The availability of this online application will improve efficiency and effectiveness in supporting the reservation process. The test procedure is carried out on a black box and the result can be displayed correctly.